Localization and delocalization of energy in a Peyrard-Bishop chain - Silva, J. M.; Drigo Filho, Elso [UNESP]; Ruggiero, José Roberto [UNESP] (Springer, 2009)
This paper studies energy localization conditions in lattices of the type proposed by Peyrard and Bishop. Homogeneous and inhomogeneous lattices are analyzed and the role of interfaces in the latter is emphasized. Simulations allowed us to identify critical energy values for the existence of localization. After a certain energy value, it is possible to observe the loss of energy localization along the chain.